The Roles of the Institution of Pesantren in the Development of Rural Society: A Study in Kabupaten Tasikmalaya, West Java, Indonesia - Muhamad Mustari (International Journal of Nusantara Islam, 2013)
Pesantrens are the oldest non-formal and traditional Islamic educational institution in Indonesia. These boarding institutions are uniquely Indonesian phenomenon, not found in other parts of the world. Nowadays, there is a widespread misjudgment that the pesantrens are said to train terrorist groups, promote Islamic fanaticism, and propagate conservative culture. Hence, some of the pesantrens are changing their paradigm, that is, from conservatism to modern-progressivism, while some others prefer to remain the same. The purpose of this study was to make an in-depth systematic analysis of the roles and contributions of pesantrens in the development of rural villages in Java, particularly in Tasikmalaya district which by itself had 761 pesantrens. This study employed the multiple case-study method. The cases were three large pesantrens and three small pesantrens, all located in Kabupaten Tasikmalaya. The pesantrens were in three categories: traditional, modern, and combination. Interview, observation, and document analysis were used to collect data. Face-to-face interviews were based on a standard check list developed for the study. The findings showed that pesantrens developed and implemented their own development plans, both for their own development and for rural development, as most pesantrens located in the rural areas.